STRATEGI PEMBELAJARAN BERBASIS TEKNOLOGI DALAM PROGRAM MADRASAH DIGITAL (STUDI KASUS DI MTS 1 MAKASSAR) - Juhri, Juhri; Mustamin, Mustamin; Zainal, Abdul Qahar; Al-Gifari, Muh.; Hidayah, M. Furqan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study is motivated by the need for Islamic educational institutions to adapt to digital transformation while maintaining their religious identity. MTsN 1 Makassar, as a pilot digital madrasah, represents both a challenge and an opportunity for teachers and students to integrate technology with Islamic values in the learning process. The research focuses on describing technology-based learning strategies implemented in the Digital Madrasah program and analyzing how Islamic values are embedded in these practices. Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis, including digital lesson plans, Learning Management System (LMS) activities, and institutional reports. Data were analyzed through reduction, display, and conclusion drawing, supported by source and methodological triangulation. The findings reveal that teachers at MTsN 1 Makassar successfully implemented interactive technology-based learning through the use of Google Classroom, Quizizz, instructional videos, and other digital media. These strategies significantly enhanced students’ motivation, participation, and collaboration while simultaneously fostering Islamic digital ethics, honesty, and responsibility. Teachers demonstrated integrative competencies aligned with the TPACK (Technological Pedagogical Content Knowledge) framework and reached the Modification–Redefinition levels of the SAMR model, where technology not only supports but transforms the learning experience. The main challenges, such as limited internet access and unequal device availability, were mitigated through offline materials and institutional support. The study concludes that the Digital Madrasah model effectively promotes adaptive, innovative, and value-oriented learning, positioning Islamic education as both spiritually grounded and technologically responsive in the digital era. ABSTRAKPenelitian ini dilatarbelakangi oleh kebutuhan madrasah untuk beradaptasi dengan transformasi digital tanpa menghilangkan identitas keislamannya. MTsN 1 Makassar sebagai madrasah percontohan digital menghadirkan tantangan dan peluang baru bagi guru dan siswa dalam mengintegrasikan teknologi dengan nilai-nilai islam. Fokus penelitian ini adalah untuk mendeskripsikan strategi pembelajaran berbasis teknologi dalam program Madrasah Digital serta bagaimana nilai-nilai Islami diimplementasikan dalam proses pembelajaran tersebut. Penelitian ini menggunakan pendekatan kualitatif jenis studi kasus, dengan pengumpulan data melalui wawancara mendalam, observasi kelas, dan analisis dokumen seperti RPP digital, aktivitas Learning Management System (LMS), serta laporan program madrasah. Analisis data dilakukan melalui reduksi, display, dan penarikan kesimpulan dengan triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa guru di MTsN 1 Makassar telah berhasil menerapkan pembelajaran berbasis teknologi secara interaktif melalui penggunaan Google Classroom, Quizizz, video pembelajaran, dan media digital lainnya. Strategi ini meningkatkan motivasi, partisipasi, dan kolaborasi siswa dalam belajar, serta menginternalisasikan nilai-nilai Islami seperti etika digital, kejujuran, dan tanggung jawab. Penerapan teknologi oleh guru menunjukkan kemampuan integratif berdasarkan model TPACK (Technological Pedagogical Content Knowledge) dan mencapai level Modification–Redefinition pada model SAMR. Tantangan utama berupa keterbatasan jaringan internet dan perangkat belajar diatasi dengan penyediaan materi offline dan dukungan kebijakan madrasah. Simpulan penelitian menegaskan bahwa madrasah digital mampu mewujudkan pembelajaran yang adaptif, inovatif, dan berkarakter Islami, sekaligus menjadi model transformasi pendidikan islam di era digital